Paralisia cerebral hemiplégica e trombofilias geneticamente determinadas - Alexandre Castelo Branco Araujo (2009)
The purpose of this study is to perform a detailed analysis about the role of the genetically determined thrombophilias as predetermining factors to the hemiplegic cerebral palsy due to ischemic stroke, approaching the main conceptual, epidemiological andphysiopathological aspects. Articles about such theme have been researched in Medline, Lilacs, Embase, Cinahl, Cochrane databases with the following keywords: ischemic stroke, antithrombin, protein C, protein S, factor V Leiden, prothrombin, hemiplegic cerebral palsy, prothrombotic, thrombophilias, thrombosis, thromboembolism. The limits were subjects up to eighteen years old and the period between 1998 and 2008. No language restriction. Hemiplegic cerebral palsy is a frequent cause for children impairment. Lately, ischemic strokes have emerged amongst the main factors, although little is known about the etiological factors involved, their interactions, physiopathologicalmechanisms and evolution. Genetically determined thrombophilias are hypercoagulability states inherited, which contribute as possible predisponent conditions for the development of such serious event with consequent brain damage. Ischemic stroke is an important cause of hemiplegic cerebral palsy. It shows high morbidity and mortality thus bringing forth strong psychological and social impact on the affected subjects and their families. Its etiology is multifactorial and has severalindefinite risk factors. Currently, the researches demonstrate that thrombophilia have physiopathological importance for the ischemic stroke and hence, hemipleg cerebral palsy. That statement is not absolute, since other studies could not prove the same findings.Resistance to activated protein C - Factor V Leiden, coagulation factor II G20210A mutation and Protein C deficiency show, at first, major relevance in children, but there have been some controversy studies in adults. New researches are necessary to elucidate the actual role ofthrombophilia as predetermining factor of ischemic stroke. Therefore, we should carry preventive and therapeutic actions besides suitable guidance and genetic counseling.